PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH DAN MINAT BACA SISWA TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VII SEMESTER GENAP SMP NEGERI 2 METRO TAHUN PELAJARAN 2016/2017 - Novita Sari; Wakijo Wakijo (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
The purpose of this study is to determine the Effect of School Library Utilization and Reading Interest on Student Learning Outcomes Integrated Students Class VII Semester Even SMP Negeri 2 Metro Year Lesson 2016/2017. The population in this study were all students of class VII SMPN 2 Metro, amounting to 240 students and samples taken using cluster random sampling technique (random sample) is the determination of samples with the draw of the class. The selected classes are the VII F class of 30 students. To know whether there is Influence of School Library Utilization and Student Reading Interest on Integrated IPS Learning Outcomes is by multiple linear regression formula.  From the data analysis of the research results using multiple linear regression formula with the calculation result of School Library Utilization of Integrated IPS Learning Outcomes is 0.923 with very close criteria, from Reading Interest to Integrated IPS Learning Outcomes is 0.707 with the criteria closely and R2 from the Effect of School Library Utilization and Interest Read on Integrated IPS Learning Results of 0.878 with very close criteria. Thus it can be concluded that there is Influence of School Library Utilization And Interest Reading To Learning Results Integrated IPS SMP Negeri 2 Metro Lesson Year 2016/2017 classified as very positive. Where students who declared complete study with KKM >75 as many as 22 students or by 87% and students who expressed incomplete learning as many as 8 students or 13%. Thus the hypothesis is accepted when the Library Utilization and Reading Interest is applied then the results of learning IPS Integrated will be better. The results of this study can be used as a reference for better learning. Keywords: Utilization of School Library, Reading Interest, And Learning Outcomes